2021
DOI: 10.3390/pr9071118
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis and Optimization of Solar-Assited Heat Pump Drying System with Waste Heat Recovery Based on TRNSYS

Abstract: In this paper, a new solar-assisted heat pump drying system with waste heat recovery and double water tanks (SCAHP) was established and the system optimized by TRNSYS and variable air volume experiment. The annual cumulative efficiency of the SCAHP (COPac), buffer tank heating efficiency (ηBT) and hot water storage tank heating efficiency (ηST) are all considered as optimization objectives, and this paper discusses the relationship between the three optimization objectives and studies the influence of hot air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…The payback period in this study is less as compared to the 5 years reported by Xie et al. ( 2021 ) for SAHPD with waste heat recovery. The difference could be due to less quantity of the annually dried products in the dryer, in which it was reported 45.99 kg compared to 1,200 kg of dried carrots, hence making less annual savings.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The payback period in this study is less as compared to the 5 years reported by Xie et al. ( 2021 ) for SAHPD with waste heat recovery. The difference could be due to less quantity of the annually dried products in the dryer, in which it was reported 45.99 kg compared to 1,200 kg of dried carrots, hence making less annual savings.…”
Section: Resultscontrasting
confidence: 54%
“…The obtained payback periods are in the range of 1.6-3.6 years for most of the SAHPD, as reported by Loemba et al (2022) when conducting a comprehensive assessment of heat pump dryers for agricultural products. The payback period in this study is less as compared to the 5 years reported by Xie et al (2021) for SAHPD with waste heat recovery. The difference could be due to less quantity of the annually dried products in the dryer, in which it was reported 45.99 kg compared to 1,200 kg of dried carrots, hence making less annual savings.…”
Section: Payback Periodmentioning
confidence: 69%
“…For multi-heat source complementary technology, many researchers have carried out systematic studies through TRNSYS simulation. For example, Xie et al [8] established a new waste heat recovery dual-tank solar heat pump drying system and optimized the system through TRNSYS and variable air volume experiments. The results showed that the mixed variable air volume model could improve the drying rate and shorten the drying cycle by 28.6-33.3% with less energy loss.…”
Section: Introductionmentioning
confidence: 99%